Advances in accounting education : teaching and curriculum innovations - Calderon, Thomas G. (Advances in accounting education, 2022)
Advances in Accounting Education is a high-quality publication of both empirical and non-empirical research that investigates vital matters related to teaching, learning, and curriculum development. By focusing on these topics, the series supports the improvement of accounting programs at colleges and universities, and fosters innovative discussion and significant contributions to faculty development. This 26th volume features 14 peer-reviewed papers surrounding four themes: capacity building and governance; curriculum and pedagogical innovations; educational tax cases and tax literacy; information technology and the curriculum. Authors explore empirical evidence on topics such as degree type and CPA exam performance, to the link between tax literacy and business experience of college students. A review of published pedagogical tax cases offers insights into their various characteristics. Finally, Volume 26 closes with a theme that explores specific ideas for incorporating new information technology developments into the accounting curriculum. Faculty with an interest in accounting education as well as accounting program administrators should find all four themes to be highly informative and interesting. Some practitioners and regulators in the accounting profession may also find useful policy-related nuggets in Volume 26.